Perception and Readiness of Pre-Service Teachers in Implementing Individualized Educational Program (IEP) in Inclusive Education - Hidayah, Anis; Mustakim, Adam; Nafisah, Durrotun; Wahono, Suparwoto Sapto; Machfudi, Moch. Imam; Arifin, Miftah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aimed to analyze: (1) pre-service teachers' perceptions of the urgency of the IEP, (2) their readiness (cognitive, affective, and skills) to design and implement it, and (3) the influence of internal and external factors on this readiness. A quantitative approach using descriptive and correlational survey methods was employed. The research subjects were 38 seventh-semester prospective teachers at universities in East Java, Indonesia. The universities were Jember Islamic University, State Islamic University (UIN Kyai Haji Ahmad Shiddiq), and Nurul Jadid University, which were selected through purposive sampling. Data were collected using a valid and reliable Likert scale questionnaire. The data analysis used was descriptive analysis and multiple linear regression. Descriptive analysis revealed that 64.5% of participants had positive readiness and perceptions. While perception of IEP urgency was high (73.7% positive), external factors like institutional support showed the lowest positive percentage (57.9%). Multiple Linear Regression indicated that internal and external factors together significantly influenced readiness (R²=0.794), with internal factors (β=0.512) being more dominant than external ones (β=0.387). The novelty of this finding underscores that while personal competence development is foundational, systemic support from teacher education institutions is equally critical for successful IEP implementation, highlighting a necessary dual focus in teacher preparation programs.